2013
DOI: 10.4102/ajod.v2i1.22
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to and facilitators of rehabilitation services for people with physical disabilities: A systematic review

Abstract: BackgroundAs health care practitioners, it is important to have an understanding of the common barriers to and facilitators of the rehabilitation services we provide.ObjectivesThis article aimed to review the relevant literature regarding barriers to and facilitators of rehabilitation services for people with disabilities.MethodArticles for the period 1990–2010 using descriptors related to rehabilitation services, barriers, facilitators and the physically disabled population were retrieved for this review.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
15

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 21 publications
3
24
0
15
Order By: Relevance
“…This may be attributed to the creation of awareness about disability issues and the rights of people with disability, with the coming into force of the Ghanaian Disability Law (Asante and Sesu, 2015). This supports a study by Mlenzana et al (2013) that health professionals exchanged information during consultation and care of people with disability.…”
Section: Discussionsupporting
confidence: 87%
“…This may be attributed to the creation of awareness about disability issues and the rights of people with disability, with the coming into force of the Ghanaian Disability Law (Asante and Sesu, 2015). This supports a study by Mlenzana et al (2013) that health professionals exchanged information during consultation and care of people with disability.…”
Section: Discussionsupporting
confidence: 87%
“…Contrary to previous studies (Kahonde et al 2010 ), the participants in this study reported a good interaction with their therapists and indicated that they received the necessary information. A review conducted by Mlenzana et al ( 2013 ) highlighted the importance of a positive caregiver-therapist relationship.…”
Section: Resultsmentioning
confidence: 99%
“…Probes were used to obtain in-depth descriptions of their perceptions and satisfaction with the services. To ensure trustworthiness (Lincoln & Guba 1985 ) in this study, the interview guide was developed after the researcher conducted a systematic review, which focused on barriers and facilitators to rehabilitation services (Mlenzana et al 2013 ). Themes that emerged from the systematic review were: financial difficulties, caregiver and therapist relationship, facility management and caregiver experience with service delivery, and were used as predetermined themes of this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In many lower-income territories, physical rehabilitation services are in short supply (Bunning et al, 2014;Wylie et al, 2016;Agho & John, 2017;Jesus et al, 2017;Krug & Cieza, 2017). Besides, in those areas, people with disabilities typically experience more financial, transportation or attitudinal barriers to access needed healthcare than people without disabilities (Mlenzana et al, 2013;Abdi et al, 2015;Neille & Penn, 2015;van Hees et al, 2015;Ganle et al, 2016;Munthali et al, 2017;Visagie et al, 2017;Vergunst et al, 2017) , even though people with disabilities usually have higher health needs, higher risks of chronic and secondary health conditions, higher cost of living, and finally, lower earnings and lower employment rates (Mitra et al, 2009;Rimmer et al, 2011;World Health Organisation and World Bank, 2011;Gudlavalleti et al, 2014;Mitra et al, 2017).…”
Section: Introductionmentioning
confidence: 99%